2017
DOI: 10.18632/oncotarget.15837
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional landscape of human cancers

Abstract: The homogeneity and heterogeneity in somatic mutations, copy number alterations and methylation across different cancer types have been extensively explored. However, the related exploration based on transcriptome data is lacking. In this study we explored gene expression profiles across 33 human cancer types using The Cancer Genome Atlas (TCGA) data. We identified consistently upregulated genes (such as E2F1, EZH2, FOXM1, MYBL2, PLK1, TTK, AURKA/B and BUB1) and consistently downregulated genes (such as SCARA5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
73
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 90 publications
6
73
2
Order By: Relevance
“…Significantly higher expression of EZH2 could be found in CRC tissues. This result was supported by our immunohistochemistry staining results and other bioinformatics analysis results based on 33 human cancer types in TCGA database, which showed that EZH2 was one of the consistently up‐regulated genes in tumour samples across various cancers . Moreover, another study found that RNA interference (RNAi)‐mediated intracellular EZH2 depletion led to blockade of the proliferation of CRC cells, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Significantly higher expression of EZH2 could be found in CRC tissues. This result was supported by our immunohistochemistry staining results and other bioinformatics analysis results based on 33 human cancer types in TCGA database, which showed that EZH2 was one of the consistently up‐regulated genes in tumour samples across various cancers . Moreover, another study found that RNA interference (RNAi)‐mediated intracellular EZH2 depletion led to blockade of the proliferation of CRC cells, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…This result was supported by our immunohistochemistry staining results and other bioinformatics analysis results based on 33 human cancer types in TCGA database, which showed that EZH2 was one of the consistently up-regulated genes in tumour samples across various cancers. 16 Moreover, another study found that RNA interference (RNAi)-mediated intracellular process malfunctions, resulting in uncontrolled cell proliferation. Of the nine up-regulated genes in cell cycle pathway, two key genes are CDK1 and CDC6.…”
Section: (D) (E) (F)mentioning
confidence: 99%
“…Conversely, most H3K27ac genome-wide studies describe a degree of locus specificity in the maintenance of H3K27ac during mitosis (Hsiung et al 2016;Li et al 2017;Liu et al 2017a;Liu et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, expression of PEG3 in colorectal patients shows statistically significant lower gene expression than matched controls from two independent studies using RNA-Seq and microarray platforms [26,27]. Its down expression is also reported to be statistically significant associated with patients' survival in various types of tumors [31]. PEG3 acts as a tumor suppressor gene by binding and promoting the degradation of β -catenin, which will consequently inhibit Wnt Signaling [32].…”
Section: Somatic Mutationmentioning
confidence: 97%